Australia and its Importance in the World Economy - Syrvatková, Radka; Kopřiva, Bohumil; Riley, Steven Del; Vysoká škola ekonomická v Praze. Fakulta managementu (2009)
The aim of my thesis is to analyze Australia's political and economic situation. My thesis consists of two parts. In the first part I describe Australia in terms of geography, and I acquaint readers with its history, especially after World War II. In the second part I deal with the current economic situation of Australia, and political system which I compare to the political system in Great Britain within the Commonwealth. In conclusion, I summarize my work and find out Australia's future strengths, weaknesses, opportunities, and threats using SWOT analysis.
Vedoucí práce: Bohumil Kopřiva
Obsahuje bibliografii
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta managementu, 2010
Rok obhajoby 2010
Keywords: dějiny; hospodářská politika; Velká Británie; Austrálie; management [obor bakal. práce]; bakalářské práce; history; economic policy; Great Britain; Australia; bachelor's theses